Evaluation of Students' Performance in the English Curriculum of the Bilingual Business Communication Degree - Figueroa Díaz, Jennifer Joan; Justiniani De Los Ríos, Marta Ixel (Panamá : Universidad Tecnológica de Panamá, 2021)
This research studies the English Knowledge and performace of the students of the bachelor' s degree in Bilingual Business Communication of the Central Campus Victor Levvi Sasso of Universidad Tecnológica de Panamá, considering the students' performace in the sixteen courses taught in English and their experience during the career, along with the professors' perspective of the issue. In the year 2020, through the second semester was framed with descriptive and exploratory type research in a transversal design. Results of this study demonstrated that: first, the students have a perception of having the English level necessary to obtain their diploma, However, the results of the English Diagnostic Test showed the opposite; second, the professors confirmed that the students had issues to have a good performance in the courses they teach; and third, the students that enrolled in the sixth semester of the career showed in the Englih Diagnostic Test a low outcome in three out of the four skills that were studied ( writing composition, listening comprehension, and reading comprehension), and grammar and vocabulary performance.
Esta investigación estudia el conocimiento y desempeño en inglés de los estudiantes de la Licenciatura en Comunicación Ejecutiva Bilingüe del Campus Central Víctor Levi Sasso de la Universidad Tecnológica de Panamá, teniendo en cuenta el rendimiento de los estudiantes en los dieciséis cursos impartidos en inglés y su experiencia durante la carrera, junto con la perspectiva de los profesores sobre lo mencionado anteriormente. Durante el segundo periodo académico del año 2020 enmarcado dentro del tipo de investigación descriptiva y exploratoria con un diseño transversal descriptivo. Los resultados del estudio demostraron que, primero, los estudiantes tienen una percepción de tener el nivel de inglés necesario para obtener satisfactoriamente su diploma, sin embargo, los resultados de la prueba diagnóstica de inglés mostraron lo contrario; segundo, los profesores confirmaron que los estudiantes tienen problemas para desempeñarse satisfactoriamente en los cursos que ellos enseñan; y tercero, los estudiantes matriculados en el sexto semestre de la carrera mostraron en la prueba diagnóstica de inglés un bajo desempeño en tres de las cuatro habilidades principales que fueron estudiadas (composición escrita, compresión oral, y compresión lectora) y su desempeño en gramática y vocabulario.
Introduction. -- Chapter 1: Description of the investigation. -- Chapter 2: Literature review. -- Chapter 3: Methodology. -- Chapter 4: Results. -- Endnotes. -- Recommendations. -- Bibliography. -- Annexes.
Tesis (
Incluye bibliografía, hojas 62-64 y anexos, hojas 65-85.
LCEBI
Jennifer Joan Figueroa Diaz.
Keywords: Ciencia y tecnología; Tesis y disertaciones académicas; Licenciatura en Comunicación Ejecutiva Bilingüe